Non-destructive multielement analysis of airborne particles byinstrumental neutron activation analysis - Sani Musa - AbdullahiMuhammad Ayuba (University of Eloued جامعة الوادي, 2022)
Adsorption of anionic dye Alizarin red S (ARS) on carbonized typha grass (CRB-TG) was studied in an equilibrium batch process. Effects of contact time, initial dye concentration, adsorbent dose, pH, and temperature on the ARS removal were tested. The adsorbent was characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and point of zero charge (PZC) methods. Equilibrium data were mathematically modelled using the Langmuir, Freundlich, Temkin and Dubinin Radushkevich (D-R) models. Kinetic of adsorption was determined by pseudo first-order, pseudo-second-order Elovich and Intraparticle diffusion models. The thermodynamics quantities of the adsorption process including ΔS (56.983J/molK), ΔH (10.909kJ/mol) and ΔG (-6.359 to -7.499kJ/mol) were calculated from Van’t Hoff plot. An optimum equilibrium removal of the anionic dye was obtained at a pH of 6, contact time of 60 minutes, low adsorbent dosage and moderate temperature. The rapid ARS adsorption verified the efficiency of CRB-TG with a maximum adsorption capacity of 46.296mg/g. The data generated were best described by pseudo-second-order kinetic model and the adsorption isotherm was favoured by Freundlich compared to other models tested. The thermodynamics parameters indicate the process to be rapid, feasible and spontaneous. The obtained results show that carbonized typha grass can be used as a readily available, low cost, eco-friendly adsorbent for the removal of anionic dyes from waste water with improved efficacy as an outstanding alternative to the commercially available adsorbents
Article
Keywords: Adsorption; Kinetics; Thermodynamics; Equilibrium; T. latifolia